2014
DOI: 10.4172/2157-7110.1000329
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality Attributes During Storage of Guava Nectar Cv. Lalit from Different Pulp and TSS Ratio

Abstract: A study was undertaken for preparation of nectar using guava cv. Lalit with respect to pulp percentage and TSS (º Brix) as per the treatments and the processed nectar was analyzed in CRD (Completely Randomized Design). Physico-chemical parameters viz., TSS, acidity, ascorbic acid, non-reducing sugars, total sugars and viscosity as well as organoleptic attributes viz., colour, flavour, taste and overall acceptability of nectar were evaluated at an interval of 2 months up to 8 months of storage. An overall resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
3
4
0
Order By: Relevance
“…This reduction was attributed to the oxidation of ascorbic acid and exposure to the light. Present results are in agreement with those of Bal et al (2014) for guava nectar, Karav et al (2015) for pomegranate juice and Liu et al (2014) for mango nectar during the storage. Also, a significant decrease in ascorbic acid during cold storage of commercial orange and grapefruit juices was reported by Kabasakalis et al (2000).…”
Section: Ascorbic Acid Total Phenolic Compounds and Antioxidant Actisupporting
confidence: 93%
See 1 more Smart Citation
“…This reduction was attributed to the oxidation of ascorbic acid and exposure to the light. Present results are in agreement with those of Bal et al (2014) for guava nectar, Karav et al (2015) for pomegranate juice and Liu et al (2014) for mango nectar during the storage. Also, a significant decrease in ascorbic acid during cold storage of commercial orange and grapefruit juices was reported by Kabasakalis et al (2000).…”
Section: Ascorbic Acid Total Phenolic Compounds and Antioxidant Actisupporting
confidence: 93%
“…Present results are in agreement with those reported by Gao and Rupasinghe (2012) for apple-carrot juice blends, Hashem et al (2014) for orange-carrot juice blends and Liao et al (2007) for carrot juice. Also, Bal et al (2014) found a significant increase in acidity in guava nectar during storage. In contrast, Gao and Rupasinghe (2012) reported that turbidity of all apple-carrot juice blends significantly increased after 21 days of cold storage.…”
Section: Total Soluble Solids Ph Titratable Acidity and Turbidity Omentioning
confidence: 89%
“…Similar types of observation for total sugar of various products have been reported by Kaushal et al (2001) in apple pomace toffees, Bhardwaj (2013) in stored kinnow juice and Bal et al (2014) in guava nectar.…”
Section: Changes In Total Sugars (%)supporting
confidence: 56%
“…1c) significantly during the storage. The increase in strain and shearing rate along with the decrease in the flow index of the product led to develop pseudo plasticity which ultimately increased the apparent viscosity of the product (Bal et al, 2014). The other possible reason could be the formation of precipitates in appetizer which was caused due to the interaction of sugars with phenols and proteins.…”
Section: Standardization Of Recipe For the Preparation Of Wild Pricklmentioning
confidence: 99%